Navigating Diversity: Supporting and Inhibiting Factors in EFL Teachers’ Implementation of Learning Style-Based Strategies - Andi Khofifah Andi Pogeng; Sukardi Weda; Muh. Hasbi; Muh.Tahir; Muh.Fakhrul Armas (Universitas Islam Negeri Palopo, 2025)
This study explores the supporting and inhibiting factors in EFL teachers' implementation of learning style-based strategies, focusing on Miss I, an EFL teacher at SMAN 2 Pangkep. The research aims to identify how Miss I accommodates students' diverse learning styles and the challenges she faces in doing so. Using a qualitative descriptive approach, the study involved classroom observations and interviews with Miss I and her students. Thematic analysis was employed to analyze the data. Findings indicate that Miss I’s willingness to adjust her teaching methods based on student engagement, along with the positive student attitudes and basic resources such as textbooks with pictures and mobile phones, played a key role in her ability to accommodate different learning styles. However, inhibiting factors included her lack of formal training in learning styles and differentiated instruction, limited classroom facilities, and passive student participation. Despite these challenges, Miss I demonstrated flexibility and creativity in her approach, though the absence of adequate training and resources limited her full capacity to address all students' needs. The study recommends future research on the impact of teacher training programs for differentiated instruction and exploring the integration of technology to support diverse learning styles in resource-constrained classrooms.